Correlations between serum and CSF pNfH levels in ALS, FTD and controls: a comparison of three analytical approaches - Wilke, Carlo; Pujol-Calderón, Fani; Barro, Christian; Stransky, Elke; Blennow, Kaj; Michalak, Zuzanna; Deuschle, Christian; Jeromin, Andreas; Zetterberg, Henrik; Schüle, Rebecca; Höglund, Kina; Kuhle, Jens; et al. (Clinical chemistry and laboratory medicine, 2019)
Background Phosphorylated neurofilament heavy (pNfH), a neuronal cytoskeleton protein, might provide a promising blood biomarker of neuronal damage in neurodegenerative diseases (NDDs). The best analytical approaches to measure pNfH levels and whether serum levels correlate with cerebrospinal fluid (CSF) levels in NDDs remain to be determined. Methods We here compared analytical sensitivity and reliability of three novel analytical approaches (homebrew Simoa, commercial Simoa and ELISA) for quantifying pNfH in both CSF and serum in samples of amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD) and control subjects. Results While all three assays showed highly correlated CSF measurements, Simoa assays also yielded high between-assay correlations for serum measurements (ϱ = 0.95). Serum levels also correlated strongly with CSF levels for Simoa-based measurements (both ϱ = 0.62). All three assays allowed distinguishing ALS from controls by increased CSF pNfH levels, and Simoa assays also by increased serum pNfH levels. pNfH levels were also increased in FTD. Conclusions pNfH concentrations in CSF and, if measured by Simoa assays, in blood might provide a sensitive and reliable biomarker of neuronal damage, with good between-assay correlations. Serum pNfH levels measured by Simoa assays closely reflect CSF levels, rendering serum pNfH an easily accessible blood biomarker of neuronal damage in NDDs.